2009
DOI: 10.1093/ije/dyn376
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature on mortality in rural Bangladesh—a population-based time-series study

Abstract: This study found that daily mortality increased with low temperatures in the preceding weeks, while there was no association found between high temperatures and daily mortality in rural Bangladesh. Preventive measures during low temperatures should be considered especially for young infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 29 publications
3
54
0
Order By: Relevance
“…To be able to formulate comprehensive heat-health action plans, it is imperative that we assess heat-related health risks in rural areas [14]; however, conducting risk assessments for rural settings can be challenging. Most rural areas, especially in underdeveloped countries, lack meteorological data due to a paucity of weather monitoring stations [15,16]. Additionally, relatively small rural populations militate against epidemiologic studies with sufficient statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…To be able to formulate comprehensive heat-health action plans, it is imperative that we assess heat-related health risks in rural areas [14]; however, conducting risk assessments for rural settings can be challenging. Most rural areas, especially in underdeveloped countries, lack meteorological data due to a paucity of weather monitoring stations [15,16]. Additionally, relatively small rural populations militate against epidemiologic studies with sufficient statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…numerous studies have reported associations between temperature and mortality as nonlinear (J-or U-shaped) relationships, highlighting the mortality effects of extreme cold or hot temperatures. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] although earlier research focused on a single city or a few cities, several time-series studies covering multiple cities or countries have recently been published. [1][2][3][4][5][6][12][13][14][15][16][17][18] Studies with multiple cities or countries allow for meaningful comparisons across geographic areas and for more accurate estimations of between-city or between-country variations, using a unified analytical framework.…”
mentioning
confidence: 99%
“…Hashizume et al (2009) find that perinatal mortality sharply increases with low temperatures. Dadvand et al (2011) conclude that extreme heat was associated with a reduction in the average gestational age of children, which is associated with perinatal mortality and morbidity.…”
Section: The Physiology Channelmentioning
confidence: 85%
“…This effect is even larger in low-income areas. Hashizume et al (2009) characterize the daily temperature-mortality relationship in rural Bangladesh and find that for the period between 1994 and 2002, a 1°C decrease in mean temperature was associated with a 3.2 percent (95 percent confidence interval: 0.9-5.5) increase in mortality, with deaths resulting from perinatal causes sharply increasing with low temperatures. In an international study of temperature and weather in urban areas using data from 12 cities in developing countries, including Mexico City and Monterrey, McMichael et al (2008) find a U-shaped temperature-mortality relationship, with significant death rate increases at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%